New Alkaloids From a Hawaiian Fungal Strain Aspergillus felis FM324 - Wang, Cong; Sarotti, Ariel M.; Zaman, KH Ahammad Uz; Wu, Xiaohua; Cao, Shugeng (Frontiers in Chemistry, 2021)
Two new alkaloids tryptoquivaline Y (1) and pseurotin I (2), together with eight known compounds (3–10), were purified from a fungal strain Aspergillus felis FM324, which was isolated from a Hawaiian beach soil sample. The absolute configuration and physicochemical data of tryptoquivaline Z (3) were reported for the first time here in this paper. Compound 1 is an uncommon tryptoquivaline analog containing a 3-O-isobutanoyl group. The structures of the new compounds 1–2 and known compound 3 were elucidated through HRESIMS, NMR spectroscopy and ECD analysis. All the compounds were evaluated for their antiproliferative, antibacterial and NF-κB inhibitory activities. Compound 4 showed weak antibacterial activity against Staphylococcus aureus, methicillin resistant Staphylococcus aureus and Bacillus subtilis with the same MIC value of 59.2 µM. Compounds 3 and 2 inhibited NF-κB with IC50 values of 26.7 and 30.9 μM, respectively.